Identification of Highly Pathogenic Microorganisms by Matrix-Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry: Results of an Interlaboratory Ring Trial - Lasch, Peter; Wahab, Tara; Weil, Sandra; Pályi, Bernadett; Tomaso, Herbert; Zange, Sabine; Kiland Granerud, Beathe; Drevinek, Michal; Kokotovic, Branko; Wittwer, Matthias; Pflüger, Valentin; Di Caro, Antonino; et al. (Journal of clinical microbiology, 2015)
In the case of a release of highly pathogenic bacteria (HPB), there is an urgent need for rapid, accurate, and reliable diagnostics. MALDI-TOF mass spectrometry is a rapid, accurate, and relatively inexpensive technique that is becoming increasingly important in microbiological diagnostics to complement classical microbiology, PCR, and genotyping of HPB. In the present study, the results of a joint exercise with 11 partner institutions from nine European countries are presented. In this exercise, 10 distinct microbial samples, among them five HPB, Bacillus anthracis, Brucella canis, Burkholderia mallei, Burkholderia pseudomallei, and Yersinia pestis, were characterized under blinded conditions. Microbial strains were inactivated by high-dose gamma irradiation before shipment. Preparatory investigations ensured that this type of inactivation induced only subtle spectral changes with negligible influence on the quality of the diagnosis. Furthermore, pilot tests on nonpathogenic strains were systematically conducted to ensure the suitability of sample preparation and to optimize and standardize the workflow for microbial identification. The analysis of the microbial mass spectra was carried out by the individual laboratories on the basis of spectral libraries available on site. All mass spectra were also tested against an in-house HPB library at the Robert Koch Institute (RKI). The averaged identification accuracy was 77% in the first case and improved to >93% when the spectral diagnoses were obtained on the basis of the RKI library. The compilation of complete and comprehensive databases with spectra from a broad strain collection is therefore considered of paramount importance for accurate microbial identification.
Keywords: testování odbornosti laboratoří; International Cooperation; Bacteria; Bacteriological Techniques; Laboratory Proficiency Testing; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Europe; mezinárodní spolupráce; bakteriologické techniky; Evropa